PENCAPAIAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA MELALUI PEMBELAJARAN GENERATIF - Hutapea, Nahor Murani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
Mathematical communication ability (MCA) has not been developed well, expected to beachieved through generative learning (GL). The study was quasi experiment with Postest Control GroupDesign, aims to assess student’s achievement of MCA, the subject was students of grade X of twoPublic Senior High School (upper and middle level), and one Private Senior High School (lower level)in Pekanbaru with a set of test instruments MCA. The Data were analyzed by t-test and one-wayAnova. The results of study show that achievement of average students’ of MCA as a whole throughGL 13.08 (59.45%), conventional learning (CVL) 11.11 (50.50%); upper school level through GL14.70 (66.82%), CVL 13.03 (59.23%); middle school level through GL 13.38 (60.82%), CVL 10.34(47%); and lower school level through GL 11.13 (50.59%), CVL 9.90 (45%); on high mathematicalprior knowledge (MPK) through GL 13.48 (61.27%), CVL 11 (50%); middle MPK through GL13.09 (59.50%), CVL 11.56 (52.55%); and lower MPK through GL 12.64 (57.45%), CVL 10.40(47.27%). Conclusion: the achievement of average students’ of MCA through GL was higher thanCVL; but as a whole, based on school level, or MPK group were middle.Keywords: achievement, mathematical communication ability, generative learning